STRATEGI INTERNATIONAL OLYMPIC COMMITTEE (IOC) DALAM MENYELENGGARAKAN OLIMPIADE TOKYO DI MASA COVID-19 - Sri Ayu Hafsa; Yessi Olivia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research will discuss the success of the International Olympic Committee (IOC) in organizing the Tokyo Olympics during the Covid-19 period. The 2020 Tokyo Olympics was postponed due to Covid-19 where all activities and gatherings of many people were restricted, so the Olympics were rescheduled and held on July 23 to August 8, 2021. The research method used in this research is descriptive qualitative. The data collection method used is document analysis. The perspective used is pluralism and uses the Standard for Organizing Events in the Covid-19 Period, namely Mass Gathering. The level analysis used is the group level. This research shows that the strategy taken by the IOC is to implement the standards for organizing events during Covid-19 as suggested by WHO. The IOC also collaborated with Pfizer on vaccine assistance and Tokyo 2020 Organizing committee who designed the Playbook as a guideline for handling Covid-19 during the Olympics. Keywords: IOC, Tokyo Olympics, Covid-19, JOC.